Latter-day saint nurses at war a story of caring and sacrifice - Rushton, Patricia (Provo, UT Religious Studies Center, Brigham Young University, 2005)
World War I -- World War II -- Cadet Nurse Corps -- Korean War -- Vietnam War -- Operation Desert Storm: The first Gulf War -- The tragedy of September 11 -- Operation Iraqi Freedom: The second Gulf War
Keywords: MORMON women -- Biography; Nurses -- Biography -- United States; military nursing -- History -- 20th century -- United States; military nursing -- History -- 21st century -- United States; Mormons -- Biography -- United States